Directions to minimization of the economic crisis influence on realization of the development of the labor potential of Ukraine - Lisohor, L. S.; Zaiukov, I. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The priority directions to minimization of economic crisis influence on realization of the development of the labor potential of Ukraine toward realization of efficient state employment policy are investigated, the base of these directions must be development and introduction of motivated national and regional programs of the population employment taking into account main trend in the development of the economy.